Temperatures and light regimes in the germination of Areca vestiaria and Areca triandra seeds - de Souza, Antonio Maricélio Borges [UNESP] (2022)
Propagation of palm trees is mainly by seeds and, in general, germination is uneven and slow, caused by several factors, such as temperature and light. We aimed to evaluate the effect of different temperature conditions and light regimes in the germination of Areca vestiaria and Areca triandra seeds. Two experiments were carried. The experimental design was completely randomized with a 5 × 2 factorial (temperature × light), with four replicates per treatment for the species A. vestiaria and five replications for A. triandra, with 25 e 20 seeds, respectively. The temperatures tested were 25, 30, 35, 20-30 and 25-35 ºC and the light regimes were presence and absence of light. The germination percentage and germination speed index were evaluated. Analysis of variance was performed using the F Test, with subsequent comparison of the means using the Tukey test (a = 0.05). For both species, there were significant differences between the temperature conditions for the studied characteristics. It was concluded that temperatures of 25 ºC, 30 ºC, 25-35 ºC and 20-30 ºC are indicated for germination of seeds of the species Areca vestiaria and, 25-35 ºC for Areca triandra, being the seeds classified as neutral photoblastics